Effect of anaerobic digestate fuel pellet production on Enterobacteriaceae and Salmonella persistence. Issue 9 (21st July 2022) - Cathcart, Ashley; Smyth, Beatrice M.; Forbes, Christina; Lyons, Gary; Murray, Simon T.; Rooney, David; Johnston, Christopher R.
Abstract: Production of digestate pellets for fuel has been identified as a promising circular economy approach to provide renewable energy and additional income to farms, while at the same time presenting the potential to divert raw digestate from nutrient‐saturated land and reduce the risk to water quality. Although previous research has investigated the feasibility of pellet production, there has been little focus on the bio‐safety aspects of the system. Little is currently known about the persistence of bacteria present in the digestate and the potential impacts on human health for those handling this product. The aim of the present research was to determine the effect that each step in the pellet production process has on bacteria numbers: anaerobic digestion, mechanical separation, solid drying, and pelletisation. Enterobacteriaceae enumeration by colony count method was used to quantify bacteria, and the presence of Salmonella at each stage was determined. The Enterobacteriaceae count reduced with each stage, and the final pelletisation step reduced bacteria numbers to below detectable levels (<10 colony forming units/g). Salmonella was only detected in the starting slurry and absent from digestate onwards. Storage of the pellets under winter and simulated summer conditions showed no reactivation of Enterobacteriaceae over time. The pelletisation process produces a digestate product with Enterobacteriaceae counts below the maximum threshold (PAS110 specification) for transport off the source farm, but care must still be taken when handling digestate pellets as complete sterilisation has not been confirmed. Abstract : Salmonella presence and Enterobacteriaceae numbers were investigated through the process of pellet production from anaerobic digestate. Salmonella was eliminated following anaerobic digestion and Enterobacteriaceae were undetectable following pelletisation, indicating that finished pellets pose reduced risk to human health compared to slurry and digestate.